Repetition, stereotype and children´s art - Ortega Cubero, Inés (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
In this article we examine the concepts underlying graphic stereotypes, which are a characteristic of outsider art. To this end, we will review a series of classic studies dealing with children’s art, as repetition and stereotype have traditionally been studied in this field. We will then try to correlate the theoretical framework derived from our critical analysis with the main ideas espoused in adult outsider art. Several significant examples In this article we examine the concepts underlying graphic stereotypes, which are a characteristic of outsider art. To this end, we will review a series of classic studies dealing with children’s art, as repetition and stereotype have traditionally been studied in this field. We will then try to correlate the theoretical framework derived from our critical analysis with the main ideas espoused in adult outsider art. Several significant examples
Keywords: stereotype; repetition; children’s art; outsider art